KEHIDUPAN SOSIAL EKONOMI PETANI IKAN KERAMBA DI DESA TANJUNG SANI MANINJAU KECAMATAN TANJUNG RAYA KABUPATEN AGAM (1991-2000) - Praditya, Doni; Sabar, Sabar; Yulia, Refni (Pendidikan Sejarah, 2014)
This Thesis discussed about the social and economic life for fish cage farmer in Tanjung Sani Village, Maninjau, Tanjung Raya subdistrict, Agam ragency (1991-2000). To make easy of the research can be made the formulation of the problem. They are (1) how is the social and economic life for fish cage farmer in Tanjung Sani village before getting job as a fish cage farmer. (2) How is the social and economic life for fish cage farmer in Tanjung Sani village after getting job as a fish cage farmer. The purposes of this research are, (1) to explain is the social and economic life for fish cage farmer in Tanjung Sani village before getting job as a fish cage farmer, (2) to explain is the social and economic life for fish cage farmer in Tanjung Sani village after getting job as a fish cage farmer. The method used in the research was historical method. This research was done in some stages. They are collecting the data (heuristik) done by critical the sources (examination), interpreting the data and historiography. After getting the data and fact accurately and valid, the research would be already typed into the thesis form. The result of the research explain that (1) the social and economic life for fish cage farmer in Tanjung Sani village before getting job as a fish cage farmer is as a fisherman, farmer in agricultural and rice field, (2) the social and economic life for fish cage farmer in Tanjung Sani village After getting job as a fish cage farmer is developing and increasing the prosperity. Job as a fish cage farmer also influence the educational level, it is proved by the childreen of a fish cage farmer can reach the educational level until college, the sociaety is already able to buy luxury properties and consumption. Another proved is also knowned from the social relationship. The condition of economic life of society in Tanjung Sani village get the increasing toward the prosperity.